Cover Image, Volume 3, Number 3, July 2021. Issue 3 (28th July 2021) - Feng, Junrun; Gao, Zhonghui; Sheng, Lin; Hao, Zhangxiang; Wang, Feng R.
Abstract : Front cover image : Garnet electrolyte is a promising candidate for all solid‐state battery. However, it suffers from interfacial problems between solid electrolyte and electrodes, and in article number 10.1002/cey2.100, Feng R. Wang et al. summary recent progress related to interfacial challenges of garnet electrolyte‐based all‐solid‐state Li‐ion batteries (garnet‐ASSLIBs), identify the properties of the interface, analyze the state‐of‐the‐art methods mitigating the challenges at the interface, and propose new opportunities in this field.